Vivir "sin dexar parte donde las cruzes españolas no hayan sido conocidas". Don Diego de Villalobos y Benavides en la administración imperial de la Monarquía hispánica - Ruiz Ibáñez, José Javier; Vallejo Cervantes, Gabriela (El Colegio de México, A.C., 2012)
This article seeks to analyze the possibilities of entering the King’s services at the end of the 16th century, resorting to the personal experience of a New Spain soldier, Don Diego de Villalobos y Benavides. Following a relative’s experience in the viceroyal administration, Don Diego returned to Spain with his family in order to serve in Flanders. He was among the first criollos to seek a military career in Europe, leaving behind him an early chronicle of his experience in theNetherlands. Case studies such as the story of this soldier, administrator and educated man, allow us to understand not only the mobility within the spaces of the Monarchy and how the royal administration worked, but also how it was proyected into the shaping of an imperial cultural policy.